2017
DOI: 10.1590/0103-6440201701573
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Biological Evaluation of Endodontic Filling Materials for Primary Teeth

Abstract: This study assessed the pH, radiopacity, antimicrobial effect, cytotoxicity and biocompatibility of endodontic filling materials for primary teeth. Zinc oxide eugenol (ZOE), Vitapex and Calen paste thickened with zinc oxide (ZO) were evaluated in comparison to an experimental MTA-based material. Radiopacity was tested using a graduated aluminum stepwedge with a digital sensor (n=5). The materials pH was recorded at 1, 4, 12 h; 1, 3, 7, 15 and 30 days (n=5). Direct contact test was used to assess the antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 21 publications
2
26
0
2
Order By: Relevance
“…The BS values obtained for the zinc oxide-based sealer (Endofill) and the mineral aggregate-based sealer (MTA Fillapex) in the present study were similar, as reported by other study (4). Despite of its low adhesion to dentin, zinc oxide-based sealers are widely used in several clinical procedures (15). This type of sealer has low resistance to compression, and low cohesion of its molecules, which can explain the low BS to dentin, and the highest number of adhesive failures verified after the push-out test (4).…”
Section: Discussionsupporting
confidence: 90%
“…The BS values obtained for the zinc oxide-based sealer (Endofill) and the mineral aggregate-based sealer (MTA Fillapex) in the present study were similar, as reported by other study (4). Despite of its low adhesion to dentin, zinc oxide-based sealers are widely used in several clinical procedures (15). This type of sealer has low resistance to compression, and low cohesion of its molecules, which can explain the low BS to dentin, and the highest number of adhesive failures verified after the push-out test (4).…”
Section: Discussionsupporting
confidence: 90%
“…5 Calen thickened with zinc oxide (Calen-ZO) has been used as a root canal filling material in the primary dentition. [6][7][8] The addition of zinc oxide (ZO) reduces the phagocytosis of Calen, thus allowing Calen to accompany the physiological resorption of primary tooth roots, and improve its physicochemical properties. 7,9 Calen-ZO induces good tissue response, 7,10 has antimicrobial activity 6 , and is more biocompatible than ZOE.…”
Section: Introductionmentioning
confidence: 99%
“…7,9 Calen-ZO induces good tissue response, 7,10 has antimicrobial activity 6 , and is more biocompatible than ZOE. 7,8 New endodontic cements have been developed, especially highlighting the advance in improved bioceramics. The main characteristics of bioceramic materials for endodontic use are their alkaline pH, shrink-free property, chemical stability within the biological environment, 11,12 biocompatibility and bioactivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the small antibacterial effects of zinc oxide eugenol and its slower adsorption rate in comparison to the roots of primary teeth, remnants exited between the root zone and apex of the tooth after exfoliation of primary teeth, causes the deformation of the underlying permanent tooth (7). Moreover, foreign body reactions and cytotoxic effects have also been reported with this type of filler (8).…”
Section: Introductionmentioning
confidence: 99%